Career Choice in Gifted Students with Interests in Stem - Gomez-Arizaga, M (Routledge, 2023)
The areas of science, technology, engineering, and mathematics have an impact on countries’ social and economic transformation, innovation, and sustainable development; women s participation, however, in science and mathematics careers, has remained scarce. This remains true for gifted women, that is, women who display high cognitive potential, which leads to less inclusive societies that squander an important part of their talent. Through a qualitative study, gender differences in the career choice process of gifted students with STEM interests were examined. Thirty students in their last year of high school (15 women and 15 men) with the above-mentioned characteristics participated by responding to an in-depth interview. Findings show that, for both genders, academic decisions are mainly determined by individual factors linked to giftedness characteristics, academic/cognitive skills and interests, and contextual factors linked to family, school, and experiences of others who study or work in the STEM areas of interest. The implications of these findings are discussed, suggesting the need to create more inclusive school environments and vocational guidance to offer these students, highlighting the urgency to promote greater female participation in STEM. © 2023 World Council for Gifted and Talented Children.